Involvement of the VGF-derived peptide TLQP-62 in nerve injury–induced hypersensitivity and spinal neuroplasticity. Issue 9 (September 2018) - Skorput, Alexander G. J.; Zhang, Xijing; Waataja, Jonathan J.; Peterson, Cristina D.; Riedl, Maureen S.; Kitto, Kelley F.; Truong, Hai; Huffman, Cecilia; Salton, Stephen R.; Fairbanks, Carolyn A.; Honda, Christopher N.; Vulchanova, Lucy
Abstract : Abstract: Neuroplasticity in the dorsal horn after peripheral nerve damage contributes critically to the establishment of chronic pain. The neurosecretory protein VGF (nonacronymic) is rapidly and robustly upregulated after nerve injury, and therefore, peptides generated from it are positioned to serve as signals for peripheral damage. The goal of this project was to understand the spinal modulatory effects of the C-terminal VGF-derived peptide TLQP-62 at the cellular level and gain insight into the function of the peptide in the development of neuropathic pain. In a rodent model of neuropathic pain, we demonstrate that endogenous levels of TLQP-62 increased in the spinal cord, and its immunoneutralization led to prolonged attenuation of the development of nerve injury–induced hypersensitivity. Using multiphoton imaging of submaximal glutamate-induced Ca 2+ responses in spinal cord slices, we demonstrate the ability of TLQP-62 to potentiate glutamatergic responses in the dorsal horn. We further demonstrate that the peptide selectively potentiates responses of high-threshold spinal neurons to mechanical stimuli in singe-unit in vivo recordings. These findings are consistent with a function of TLQP-62 in spinal plasticity that may contribute to central sensitization after nerve damage. Abstract : Supplemental Digital Content is Available in the Text.The study provides evidence for a function of the VGF-derived peptide TLQP-62 in spinal plasticity that may contribute to central sensitization after nerve damage.